2014
DOI: 10.1186/1471-2431-14-279
|View full text |Cite
|
Sign up to set email alerts
|

Long term follow up of high risk children: who, why and how?

Abstract: BackgroundMost babies are born healthy and grow and develop normally through childhood. There are, however, clearly identifiable high-risk groups of survivors, such as those born preterm or with ill-health, who are destined to have higher than expected rates of health or developmental problems, and for whom more structured and specialised follow-up programs are warranted.DiscussionThis paper presents the results of a two-day workshop held in Melbourne, Australia, to discuss neonatal populations in need of more… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
124
0
10

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 128 publications
(137 citation statements)
references
References 96 publications
3
124
0
10
Order By: Relevance
“…That cognitive development can be predicted from age 2 years is important information for health practitioners and validates existing efforts to monitor these children around this time to plan and provide appropriate support. 52 Yet, it is important to realize that these …”
Section: Figurementioning
confidence: 99%
“…That cognitive development can be predicted from age 2 years is important information for health practitioners and validates existing efforts to monitor these children around this time to plan and provide appropriate support. 52 Yet, it is important to realize that these …”
Section: Figurementioning
confidence: 99%
“…1,2 Early identification of developmental delay is essential, as timely intervention has been consistently associated with improved cognitive outcomes. 1,2 Early identification of developmental delay is essential, as timely intervention has been consistently associated with improved cognitive outcomes.…”
mentioning
confidence: 99%
“…1,2 Early identification of developmental delay is essential, as timely intervention has been consistently associated with improved cognitive outcomes. 1,6 However, because it is costly, lengthy, and requires trained personnel, a valid alternative tool that can effectively identify developmental delay is needed. 1,6 However, because it is costly, lengthy, and requires trained personnel, a valid alternative tool that can effectively identify developmental delay is needed.…”
mentioning
confidence: 99%
“…Although health care professionals can provide regular follow‐up assessments of all children born preterm to support screening and early identification of problems in social competence (Doyle et al, ), future studies are necessary to clarify what (and for whom) interventions are indicated. Moreover, including such information in future studies may shed light on the impact of specific interventions on children's social outcomes over time.…”
Section: Discussionmentioning
confidence: 99%